The machadian paideia in The posthumous memoirs: from Achilles to Bras Cubas - Ramos, Maria Celeste Tommasello (ITINERÁRIOS – Revue de Littérature, 2010)
This study analyzes the allusions to the mythological hero Achilles, from Homer’s The Illiad, focusing on the intertextual dialogue with the classic epopoeia built by Machado de Assis in The posthumous memoirs of Bras Cubas, in order to peform a disautomatization of the reader, as a process of education called paideia by the Greek.